Can individuals be influential in driving sustainable and responsible investing? - Nkomo, Juliana (Research of GSB, 2018)
Trust law has hindered beneficiaries from exerting their voice in the administration of their funds. Yet, individuals do have opinions on how they want their funds to be invested and wish to direct the investments to align with their values. For a majority of individuals, this influence is mainly through their retirement fund investments. However, trust law means that the ultimate power to decide on the investment process rests in the hands of trustees to act on behalf of all beneficiaries. And trustees also further delegate most investment decisions to the investment managers. The findings of this research, as other researchers have also found, suggests that individuals who have some knowledge of SRI show a greater willingness to invest in sustainable funds. It also suggests that after choosing the type of funds that they wish to invest in, individuals place a lot of trust in their trustees to act in their best interests by investing responsibly. The research explores the various dynamics that are at play that explain individual behaviour and attitudes towards financial planning with regards to their retirement investments. The implications of my findings may have relevance in understanding what drives individuals to become active in the investment arena and may serve as a harbinger to changes in fiduciary relationships as we know them. Further research can be done in this area that will assist policy makers to consider regulation changes that could lead to the greater inclusion of final beneficiaries in the investment management process.